Book Review: Poverty and Development: Problems and Prospects - Paddison, Brendan (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Book Review: Poverty and Development: Problems and Prospects, edited by Michal Apollo and Pahlaj Moolio eds., 2021, Channel View Publications.